If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-6 + 3y) + -7y = 5 (-6 * -4 + 3y * -4) + -7y = 5 (24 + -12y) + -7y = 5 Combine like terms: -12y + -7y = -19y 24 + -19y = 5 Solving 24 + -19y = 5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -19y = 5 + -24 Combine like terms: 24 + -24 = 0 0 + -19y = 5 + -24 -19y = 5 + -24 Combine like terms: 5 + -24 = -19 -19y = -19 Divide each side by '-19'. y = 1 Simplifying y = 1
| 1/5x+11=6 | | (x+16)+(x+5)=x+2 | | 1/3a+11=9 | | (y-3)(4y+2)= | | 6x-4=5x-8 | | 22/3/11/6 | | 2b(b^2+3b+1)= | | (5s^2)+34s+45=0 | | 9w-14=94 | | 10x-3(-2+6x)=-2 | | (5s^2)+34s+35=0 | | 60=8.5x+6y | | 7(-14-2y)=-14 | | -3x^2-3=-27 | | -2x+5+x=-2 | | 37=8x-35 | | (3xyz^4)(3x^5z^5)= | | y=9+1 | | 10n-4=56 | | x=-16x^2+4x+26 | | 3B+4B+B= | | 2(-8)+4y=16 | | 14x+3y-180=0 | | (x-7)(x-5)= | | 11-3w+w^2= | | 2+y=2x+2 | | (2x+4)x(2x+4)= | | 2*2+7y=14 | | 3+y=-5 | | 3k+5=3k+1 | | (7+v)(2v-5)=0 | | -2x+9=3x-1 |